Evaluation of sorghum accessions from Ethiopia and Mali against Fusarium thapsinum - Prom, Louis K; Erpelding, John E (Journal of Tropical Agriculture, 2013)
Thirty-eight sorghum accessions from Ethiopia and Mali along with resistant (Sureno and SC719) and susceptible (RTx430 and RTx2536) checks were evaluated in replicated plots for resistance against Fusarium thapsinum at Isabela, Puerto Rico. Environmental conditions such as temperature, relative humidity, and rainfall during this study, especially at and after physiological grain maturity were optimal for grain mold development. Highly significant negative correlations were observed between grain mold severity ratings in the field and on threshed grains with germination rate, indicating that germination rate was adversely affected when challenged with F. thapsinum. Of the 38 accessions tested, 18 accessions were either highly susceptible or susceptible to the pathogen. Accessions PI525954, PI276841, and PI276840 exhibited lower mean grain mold severities and higher germination rates when compared with the resistant checks Sureno and SC719. The aforementioned accessions may possess grain mold resistant genes and further studies are underway to determine the resistance mechanisms.